Human Capital, Higher Education Enrolment and Economic Growth in the SSA Countries (Panel Model Approach) - Akinola G. W.; Bokana K. G. (Journal of Economics and Behavioral Studies, 2018)
This study offers exploratory analysis on the relationship among human capital, higher education enrolment and economic growth in SSA countries. With data from twenty-two African countries across the four economic blocs, five variables which include human capital formation, capital stock, employment rate, total factor productivity and higher education enrolment were regressed against gross domestic product per capital. Panel analysis which includes fixed and random effects analyses were carried out. We report results from fixed effect (within) regression as Hausman test suggests. It was discovered that SADC countries perform better among the four economic blocs. To further study individual country specific effects, we employ least square dummy variables (LSDV). Sixteen countries out of twenty-two exhibit specific effects. Our findings revealed that enrolment rate of higher education in SSA have a very weak relationship with economic growth in the SSA countries. This reflects why there is a weak relationship between economic growth and the total factor productivity and consequently negative consequential effects on our total factor productivity. The main policy implication is that for SSA countries to maintain sustainable economic growth, home based human capital must be given a priority in the form of increased higher education budget and financing.